2019
DOI: 10.4236/aim.2019.98046
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetes from Soil of Lachung, a Pristine High Altitude Region of Sikkim Himalaya, Their Antimicrobial Potentiality and Production of Industrially Important Enzymes

Abstract: Investigations on actinomycetes are profoundly significant area of research since they form major resource for bioactive compounds, antimicrobials, anticancer agents, immunosuppressants, and biological control agents. A total of 59 actinomycetes were isolated from the soil sample collected from Domang, Lachung, North Sikkim, Sikkim, India. Out of the total isolates, 26 isolates with unique and distinct characteristic features were selected and analysed for antimicrobial activity as well as extracellular enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Out of the 22 isolates, 12 (54%) presented antagonistic activity towards at least one microorganism-test, 11 (50%) isolates exhibited antifungal activity and 6 (27%) isolates showed antibacterial antagonism. Our results corroborate with those obtained by Singh et al (2019), where they found that 23% of the isolates had antibacterial activity, while 47% were able to inhibit fungi. However, Boudmagh et al (2005) reported that, among the 27 isolates of arid soil, only 7% showed antifungal activity.…”
Section: Screening Of Antagonistic Isolatessupporting
confidence: 92%
See 1 more Smart Citation
“…Out of the 22 isolates, 12 (54%) presented antagonistic activity towards at least one microorganism-test, 11 (50%) isolates exhibited antifungal activity and 6 (27%) isolates showed antibacterial antagonism. Our results corroborate with those obtained by Singh et al (2019), where they found that 23% of the isolates had antibacterial activity, while 47% were able to inhibit fungi. However, Boudmagh et al (2005) reported that, among the 27 isolates of arid soil, only 7% showed antifungal activity.…”
Section: Screening Of Antagonistic Isolatessupporting
confidence: 92%
“…Several studies on the antagonistic activity of rhizospheric Streptomyces have been documented (Khamna et al 2009;Anwar et al 2016;Aouar et al 2016;Sharma and Manhas, 2020) since it is the largest and the active genus among actinobacteria, and 75% of biologically active compounds are produced by members of this genus (Singh et al 2019). However, to our knowledge, very few publications are available in the literature that explores antagonistic activity of S. albidoflavus, S. enissocaesilis, and most particularly S. flaveus.…”
Section: Enissocaesilismentioning
confidence: 99%
“…Also, Jeffrey (2008) [54] isolated 62 actinomycete isolates from the soil of Sarawak while Streptomyces atrovirens was isolated from the soil of Korea [55] while the isolated actinomycetes from different biotopes of Punjab, India showed a broad spectrum of antimicrobial activity [26]. Furthermore, 26 actinomycete isolates from Domang, India were obtaind, 12 (47%) of them had antifungal activity while 6 (23%) has antibacterial activity [56]. In addition, the threeisolated Actinobacteria showed broad-spectrum activity against Gram-positive and Gram-negative bacteria obtained from a soil sample, collected from Mount Everest [57].…”
Section: Important Secondary Metabolites Produced By Actinomycetesmentioning
confidence: 99%
“…For long-term preservation, the purified colonies were scraped from agar plates using a scraper with 15% glycerol buffer solution, transferred to a sterile cryovial, and then stored at −80°C. The strain was incubated in SCA medium for 7 days at 28°C, and a single colony was incubated in casein-starch-peptone-yeast extract-malt extract (CSPY-ME) broth with shaking at 120 rpm at 28°C for 7 days ( 12 ). Genomic DNA from SJ1-7 was extracted using a MagAttract high-molecular-weight DNA kit (Qiagen, Hilden, Germany) as instructed by the manufacturer.…”
Section: Announcementmentioning
confidence: 99%